BASEL III REQUIREMENTS AND THEIR IMPACT ON THE ACTIVITIES OF COMMERCIAL BANKS IN UZBEKISTAN - Haydarov Otayor Kholmurod o’g’li (Modern American Journals, 2025)
This article examines the Basel III requirements and their implications for the activities of commercial banks in Uzbekistan. The study highlights the key elements of Basel III, including capital adequacy standards, liquidity ratios, and risk management mechanisms, and analyzes their relevance to the Uzbek banking sector. Particular attention is paid to the challenges and opportunities associated with the implementation of Basel III, such as strengthening the capitalization of banks, improving financial stability, and enhancing risk-based supervision. The findings suggest that while Basel III requirements impose stricter regulatory standards, they also contribute to the long-term resilience and competitiveness of Uzbekistan’s commercial banks in a rapidly changing financial environment.